PENGEMBANGAN FORMULA BERBASIS BISKUIT PMT DAN UBI JALAR UNGU SEBAGAI ALTERNATIF MAKANAN TAMBAHAN UNTUK BALITA DENGAN BERAT BADAN TIDAK NAIK 2 KALI BERTURUT-TURUT (2T) - Mufidah, Lailiyah Imro'atul (Poltekkes Kemenkes Semarang, 2022)
Background: The prevalence of malnutrition and severe malnutrition in Indonesia is still quite high. Modification of PMT for toddlers made from PMT biscuits and purple sweet potato was made to fulfill the nutritional needs of toddlers as supplementary food feeding.Â Purpose: Modified PMT for toddlers made from PMT biscuits and purple sweet potato for toddlers who don't gain weight 2 times in a row (2T).Â Methods: This type of research is an experimental study with a completely randomized design, consisting of 3 levels of treatment with a ratio of purple sweet potato: PMT biscuits, which is 60:40; 50:50 ; 40:60. The sampling technique used purposive sampling of as many as 15 panelists. Empirical calculations using the Table of Composition of Food Ingredients and the Ms. Ecel 2010. Excel 2010. It was held from January to March at the Mulyorejo Health Center. The variables studied were the content of energy, protein, fat, carbohydrates, iron, vitamin A, and organoleptic quality (color, aroma, taste, texture), SAA, MCT, and NPU values. Statistical analysis using the Kruskal Wallis test.Results: The PMT modified formula that had been made did not find a significant effect on the addition of purple sweet potato to the color (p=0.843), aroma (p=0.895), and texture (p=0.999) between treatments. There was a significant effect on the taste of the biscuit sweet potato balls (p=0.043). The value of energy, protein, fat, carbohydrates, iron was higher at P3 and vitamin A was higher at P1. The best treatment level was P3 with an energy density of 3.3 Kcal/gram (medium), SAA value of 107.9%, MCT 78.2%, and NPU value of 84.4%.Â Conclusion: Modification of PMT at the P3 treatment level (40% purple sweet potato and 60% PMT biscuits) can be used as an alternative supplementary food feeding for toddlers because it provides colors, aromas, tastes, and textures that are acceptable to toddlers.